GAMBARAN KLINIS GANGGUAN KOAGULASI DAN PARAMETER KOAGULASI PADA PASIEN TERKONFIRMASI COVID-19 - AMELIA AMANDA; RATIH YULISTIKA UTAMI (JURNAL ILMIAH KOHESI, 2023)
The corona virus is an infectious disease in humans caused by Severe Acute Respiratory Syndrome Corona-Virus-2 (SARS-CoV-2). Patients who are confirmed COVID-19 checked status are his coags. In most patients, COVID-19 has haematologic abnormality, it is known through the examination of the peripheral blood in the form of leukopenia, decreased the number of eosinophil, thrombocytopenia, anemia, increase in the ratio of neutrophils, enhancement of the LED, and coagulation parameters include D-dimer, aPTT, PT, platelets and fibrinogen. The production of proinflammatory cytokines, increased damage-associated pattern molecules, the mechanism of cell death and damage to the vascular endothelium is a major cause of coagulation disorders occurs when the infection is heavy. This study aims to determine the clinical picture of the disorder of coagulation and coagulation parameters in patients with confirmed COVID-19. This research uses descriptive method using secondary data from medical record. In this research, there are clinical disorders of coagulation dominated by purpura (13,5%) and skin (11,5%), while the parameters of coagulation, which dominate the d-dimer (of 86.5%) and thrombocytopenia (32,7%). The clinical picture most often found in patients with COVID-19 with coagulation disorders is purpura and parameters of coagulation of the most rising is d-dimer.